UTILIZATION OF HIGH-VOLUME FLY ASH AS A SUPPLEMENTARY CEMENTITIOUS MATERIAL IN ENVIRONMENTALLY FRIENDLY CONCRETE - Yohans Sunarno; Parea Rusan Rangan; Ermitha Ambun; Andi Asiz; Miswar Tumpu; Astri Rinanti; Lisa Oksri-Nelfia (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Innovations in material technology are expected to reduce the use of commercial cement and replace it with other environmentally friendly materials with the same performance as normal concrete. Aim: This study aim to analyze the mechanical property of High-Volume Fly Ash Concrete (HVFAC) using F class fly ash with different mix percentages. Methodology and Results: The experiment was conducted in laboratory scale. Four variations of test specimens consisted of: 1 variation (F0), which is conventional concrete with 100% Portland cement as control specimen, and three variations of HVFC (F70, F80, and F90), which were made with fly ash content (%) 70, 80, and 90 of total cementitious. Fresh concrete testing to determine workability, while hard concrete testing is done by density and compressive strength tests at the age of 3, 7, and 28 days on specimens that have been treated with the water submerged curing method. Conclusion, significance, and impact of study: All HVFAC specimens fulfill the Self Compacting Concrete (SCC) category. The compressive strength test results at 28 days showed that the addition of fly ash percentage caused a decrease in compressive strength values in all HVFAC variants, but still exceeded the minimum requirements of high and medium quality concrete. All HVFAC variations meet the requirements of ASTM C618-23 based on the evaluation of Strength Activity Index (SAI) values at 7 and 28 days of age. The utilization of 90% fly ash as a cement substitute resulted in an environmentally friendly concrete product based on the concept of cleaner production.